Sericite Insights: Current Perspectives on Properties and Applications - Aslan Aras, Ayca; Karaduman, Emre (SPRINGER HEIDELBERG, 2025)
Sericite, a fine-grained mica belonging to the phyllosilicate group, has emerged as a noteworthy material due to its unique physicochemical characteristics, widespread natural abundance, cost-effectiveness, and environmentally friendly nature. Unlike general references to clays, which may encompass a broad spectrum of fine-grained particles with diverse structural and chemical properties, sericite exhibits a well-defined mineralogical identity and a consistent layered structure that make it suitable for a wide range of functional applications. Its lamellar morphology, high aspect ratio, low swelling tendency, and reactive surface chemistry contribute significantly to its performance in fields such as ceramics, surface coatings, building materials, personal care products, and environmental remediation. This review presents a focused and critical overview of sericite, aiming to distinguish its physicochemical features from those of other clay-based materials while emphasizing its potential value in both traditional and emerging industrial sectors. By compiling and analyzing recent experimental and theoretical studies, this work contributes to a deeper understanding of sericite's capabilities, highlights existing research gaps, and outlines possible directions for future exploration in advanced material development.
Keywords: Sericite; Pigment; Polymer-clay composites; Wastewater treatment; Biological applications; ROOM-TEMPERATURE SYNTHESIS; TIO2 COATING LAYERS; CLAY-MINERALS; WASTE-WATER; ADSORPTION CHARACTERISTICS; PHOTOACTIVITY INHIBITION; NUTRIENT DIGESTIBILITY; MECHANICAL-PROPERTIES; GROWTH-PERFORMANCE; THERMAL-PROPERTIES; Metallurgy & Metallurgical Engineering; Mining & Mineral Processing